IMPROVE PERFORMANCE SINKS IRAQI USING SYSTEM EVALUATION BANKER AMERICAN CAMELS - Mohammed Abdulrasoul; Ahmed Hassan Ali; Hussein Thamer Kazem (Scholars Digest Publishing, 2023)
The study aimed to evaluate the performance of the Bank of Baghdad using the method CAMELS, and the study relied on evaluating the performance of banks using the CAMELS method in terms of capital adequacy, asset quality, profitability, liquidity, and finally the management component., and to achieve the objectives of this study, and to apply the research in the field and achieve its hypotheses, the Bank of Baghdad, which is listed on the Iraq Stock Exchange, was chosen as a research community, representing a “sample for the fiscal years.” (2015-2017), and the study concluded that the use of the CAMELS system leads to detecting defects in banks and determining their soundness, as well as leading to improving financial control and giving indicators about the financial position of the bank and better identifying its strengths and weaknesses. The study recommended the necessity of adopting modern systems in evaluating the performance of the bank and financial departments to find out the real performance of banks and reduce problems.
Keywords: CAMELS Model, Performance evaluation, banking performance.